Sensory Integration Used with Children with Asperger’s Syndrome - Smith, Analisa L. (Journal of the American Academy of Special Education Professionals, 2010)
Sensory Integration Program on Children with Asperger’s Syndrome This literature review will document the effects of a parent implemented Sensory Integration Program upon children diagnosed with Asperger’s Syndrome in order to discern its influence upon these children’s overall ability to attend to learning and social development. The infrequency of research on Asperger’s Syndrome and sensory-based programs indicates a need for further study into the potential relationship between evaluation regarding Asperger’s Syndrome and sensory-based approaches. The following literature review reflects the findings of current research within the fields of psychology, education, neurology, medicine, and occupational therapy as they pertain to Asperger’s Syndrome.